Investigation of The Extent To Which Tourists Behave In Ways To Protect Environmental In The Community-Based Tourism Sector - Ismulyati, Sri; Ngarbingan, Hubertina Karolina; Ginting, Ginta (Yayasan Ilomata, 2025)
The study aims to analyse determinant factors influencing environmental responsibility in the tourism sector, especially community-based tourism (tourism villages). It explores the influence of place attachment, place identity and environmental knowledge on tourists' environmental responsibility by using socially responsible behaviour and personal norms as moderating variables. The quantitative research method tested casual hypotheses as unified model data from 210 tourists who visited 3 tourist villages in the Yogyakarta area, namely Bleberan, Pakarsari and Nglinggo. The data was analysed using SEM-LISREL 8. Research findings revealed that place attachment, identity, and environmental knowledge directly influence responsible behaviour. The study also found that destination social responsibility moderates the influence of place dependence on environmental responsibility, but it does not moderate the influence of place identity on environmental responsibility. An interesting finding from this research is that personal norms moderate the influence of environmental knowledge on responsible behaviour. Research findings can contribute to understanding tourists' environmental responsibility by comprehensively using a unified structural model, considering aspects of place attachment and knowledge about the environment as determinants that are strengthened by social responsibility and personal norms that influence responsible tourist behavior.